2003
DOI: 10.1182/blood-2002-06-1847
|View full text |Cite
|
Sign up to set email alerts
|

Role of the intracellular domains of GPIb in controlling the adhesive properties of the platelet GPIb/V/IX complex

Abstract: Glycoprotein (GP)Ib

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
44
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 39 publications
1
44
0
Order By: Relevance
“…Whole blood (5 l) drawn from the mouse tail was diluted 1 to 10 in Tyrode's buffer (137 mM NaCl, 2 mM KCl, 12 mM NaHCO 3 , 0.3 mM NaH 2 PO 4 , 1 mM MgCl 2 , 2 mM CaCl 2 , 5.5 mM glucose, 5 mM HEPES, pH 7.3) containing 0.35% human serum albumin and hirudin (100 U/ml) and incubated with an Alexa-647-conjugated rat monoclonal antibody against mouse glycoprotein Ib␤ (2 g/ml) (Perrault et al, 2003) and Alexa-488-conjugated fibrinogen (20 g/ml) for 10 min at 37°C, in the presence of either PAR-4 peptide (1 mM) or vehicle (plain Tyrode's buffer). Samples were then fixed for 20 min in plain Tyrode's buffer containing 2% paraformaldehyde.…”
Section: Measurement Of the Binding Of Alexa-488-labeled Fibrinogen Tmentioning
confidence: 99%
“…Whole blood (5 l) drawn from the mouse tail was diluted 1 to 10 in Tyrode's buffer (137 mM NaCl, 2 mM KCl, 12 mM NaHCO 3 , 0.3 mM NaH 2 PO 4 , 1 mM MgCl 2 , 2 mM CaCl 2 , 5.5 mM glucose, 5 mM HEPES, pH 7.3) containing 0.35% human serum albumin and hirudin (100 U/ml) and incubated with an Alexa-647-conjugated rat monoclonal antibody against mouse glycoprotein Ib␤ (2 g/ml) (Perrault et al, 2003) and Alexa-488-conjugated fibrinogen (20 g/ml) for 10 min at 37°C, in the presence of either PAR-4 peptide (1 mM) or vehicle (plain Tyrode's buffer). Samples were then fixed for 20 min in plain Tyrode's buffer containing 2% paraformaldehyde.…”
Section: Measurement Of the Binding Of Alexa-488-labeled Fibrinogen Tmentioning
confidence: 99%
“…30,31 Although the precise mechanisms of these effects remain unclear, RAM.1 does not seem to prevent VWF binding to GPIbα through a steric hindrance notably supported by the fact that a Fab fragment of this antibody had a similar effect. 30 It has recently been reported that RAM.1 did not modify VWF binding to GPIb-IX reconstituted in phospholipid bilayer nanodiscs, further suggesting that the effect of RAM.1 may not be attributable to direct interference with the VWF-GPIbα interaction.…”
mentioning
confidence: 99%
“…[3][4][5][6][7] How this receptor complex mediates signaling in both directions is not clear, but recent work has suggested the likely interaction between the Ib␣ and Ib␤ subunits as a potential key element of the mechanism. [8][9][10] Thus, understanding the interaction between GP Ib␣ and GP Ib␤, and in general the organizing principle of the GP Ib-IX-V complex, will help to unveil the mechanism underlying transmembrane signaling mediated by the complex.It is widely accepted that the GP Ib-IX-V complex contains 7 subunits composed of 4 different polypeptides: Ib␣, Ib␤, IX, and V with a respective stoichiometry of 2:2:2:1. [11][12][13][14][15] Each subunit is a type I transmembrane protein.…”
mentioning
confidence: 99%
“…[35][36][37][38][39] Both interactions are important to the function of the GP Ib-IX-V complex. [3][4][5]8,9,40 14-3-3 is a dimer, and disrupting 14-3-3 dimerization decreases its affinity for the GP Ib-IX complex but not the isolated peptide containing the Ib␣ cytoplasmic domain. 41 On the basis of the ␣␤ heterodimeric model for GP Ib, it was thought that 2 monomers in the 14-3-3 dimer interact with the Ib␣ and Ib␤ cytoplasmic domains, respectively, with the implicit assumption that one 14-3-3 dimer interacts with one GP Ib complex.…”
mentioning
confidence: 99%